2002
DOI: 10.1002/jemt.10017
|View full text |Cite
|
Sign up to set email alerts
|

Expression and plasticity of glutamate receptors in the supraoptic nucleus of the hypothalamus

Abstract: Magnocellular neuroendocrine cells (MNCs) of the supraoptic nucleus of the hypothalamus (SON) produce and release the hormones vasopressin (VP) and oxytocin (OT) in response to a variety of stimuli to regulate body water and salt, parturition and lactation. Hormone release is influenced by the pattern of neuronal firing of these MNCs, which, in turn, is governed by intrinsic conductances and synaptic inputs, including those mediated by the neurotransmitter glutamate. Functional and molecular evidence has confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 112 publications
0
12
0
1
Order By: Relevance
“…Glutamatergic receptors are divided into ionotropic and metabotropic receptor subfamilies. Ionotropic receptors act as glutamate‐gated cation channels, whereas metabotropic receptors modulate the production of second messengers via G proteins and affect other ion channels as well as intracellular processes (Pak and Curras‐Collazo, 2002). The ionotropic receptors are classified into two types according to agonist selectivity and amino acid homology: N‐methyl‐D‐aspartate (NMDA) receptors and non‐NMDA receptors, which are subdivided into amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionate (AMPA) and kainate (KA) subtypes (Hollmann and Heinemann, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamatergic receptors are divided into ionotropic and metabotropic receptor subfamilies. Ionotropic receptors act as glutamate‐gated cation channels, whereas metabotropic receptors modulate the production of second messengers via G proteins and affect other ion channels as well as intracellular processes (Pak and Curras‐Collazo, 2002). The ionotropic receptors are classified into two types according to agonist selectivity and amino acid homology: N‐methyl‐D‐aspartate (NMDA) receptors and non‐NMDA receptors, which are subdivided into amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionate (AMPA) and kainate (KA) subtypes (Hollmann and Heinemann, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The 5a-and 5b-PIC are effective as positive and negative modulators of N-methyl-D-aspartate receptors (NMDA-R) respectively (Park-Chung et al 1997, Weaver et al 2000. The activation of NMDA-R in hypothalamic magnocellular neuroendocrine cells of the supraoptic nucleus may induce oxytocin production (Pak & Curras-Collazo 2002), resulting in onset of parturition.…”
Section: Introductionmentioning
confidence: 99%
“…The non‐NMDA receptors are further divided into α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionate (AMPA) and kainate (KA) receptor subtypes (Hollmann and Heinemann,1994). Metabotropic glutamate receptors (mGLURs) are coupled to G‐protein and activate second messengers and can affect other ion channels as well as intracellular processes (Pak and Curras‐Collazo,2002). Immunohistochemical and pharmacological studies have shown that the hypothalamus, among areas involved in cardiovascular control, contains high levels of glutamate and ionotropic glutamatergic receptors (Meeker et al,1994; Singewald and Philippu,1996).…”
mentioning
confidence: 99%